Evaluation of the Peace and Order and Public Safety Plan: Its Relation to the Crime Prevention Priority Issues of the Province of Albay - Breva Jr., Domingo (JPAIR Multidisciplinary Research, 2020)
Peace is described as an environment where individuals and communities are able to develop their potentials fully and attain progress and freely exercise their rights with due regard for others while being equally mindful of their responsibilities. The Peace and Order and Public Safety Plan is a three-year plan consisting of programs and activities to promote peace and order and public safety in a particular locality and consolidated Integrated Area/Community Public Safety Plan of the cities and municipalities within the province as specified in DILGMC no. 2015-128. A quantitative descriptive approach was used to examine the relevance and effectiveness of the POPS Plan in addressing the problems of criminality in the province of Albay. Members of the community, police officers of the province, and barangay officials were the respondents. Results revealed that the peace and order councils’ action on the efforts of the government to address the crime problems is relevant. With this belief, the respondents participate in the effective implementation of the POC’s POPS Plan to address the problems of criminality. Hence, it is recommended that the policy planners of the government should seek criminological knowledge from criminologists in formulating dependable peace and order and public safety plan.